Economic and financial feasibility of a biorefinery for conversion of brewers' spent grain into a special flour - Iliane Colpo; Denis Rasquin Rabenschlag; Maria Soares de Lima; Mario Eduardo Santos Martins; Miguel Afonso Sellitto (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study aims to evaluate the financial and economic feasibility of implementing a biorefinery to process the solid waste, called brewers' spent grain, generated in the production of craft beer into special flour. In addition, to present a path for open innovation in the possibility of replication of the process and technology used in the plant. The inappropriate disposal generates an environmental problem, but individually, depending on the production volume of the brewery, the cost of processing the waste can be unfeasible. On the other hand, such waste embeds a high nutritional value for human food. This study followed the precepts of the circular bio-economy and industrial symbiosis strengthening of sustainable development. The research method is the Monte Carlo simulation, including four different scenarios and projections. The results indicate the financial and economic viability of industrial plants-biorefineries-for the transformation of the residue into special flour in three of the four scenarios studied in the five-year cycle. In the Monte Carlo simulation, no losses are evident in any of the 10,000 interactions. The sensitivity analysis demonstrates that the sensitivity of the supply is slightly higher than the price of the final product. Results may be useful to support the development of new, innovative products relying on collaboration among internal and external partners and open innovation concerns.
Keywords: 650; biorefinery; brewers' spent grain; economic feasibility; open innovation; special flour